Ethanol Production from Corn Contaminated with Fumonisins: A Preliminary Economic Analysis Including Novel Processing Alternatives - Sosa, María Angélica (2013)
In this work, technical and economical feasibility of bioethanol production from corn with high concentrations of fumonisins is analyzed. Based on data obtained from a limited number of experiments, the cost data of ethanol facilities and conceptual design methods maximum prices for corn contaminated with fumonisins are estimated. The scope of the analysis includes average ethanol concentrations in the fermentor in a range of 6 wt % and 3 wt % for noncontaminated corn and strongly contaminated corn (1400 ppm), respectively. The maximum price for contaminated corn varies from 66% to 33% of the fumonisins-free feedstock cost, according to the level of contamination. The performance of the continuously operated process was also analyzed considering the coupling of the fermentor with a pervaporation unit for continuous ethanol separation. Estimations were made for a volumetric productivity of alcohol of 7.8 kg/(m3 h) and membrane flux (0.9 kg/(m2 h)) and selectivity (S = 5) corresponding to a commercial PDMS membrane for a level of 6 wt % ethanol in the stirred-tank fermentor. Results show that an increase of 100% in the membrane flux with a constant value for the selectivity is required to make the continuous alternative attractive.